Gender and science in Portugal - Amâncio, L. (Portuguese Journal of Social Science, 2003)
The situation of women in science in Portugal stands out as a particular case in international comparisons. The argument of this article is that this case is not so particular after all. To pursue this argument, gender and science is approached in two ways. In the first part historical and social factors that may have contributed to the significant presence of women in science will be discussed. The second part focuses on scientific careers and institutions, especially universities, and aims at unveiling gender processes that have been evidenced by research on gender and science in other countries. Throughout the article, evidence will be presented that shows that despite some specificities pertaining to the rapid process of modernization experienced by Portugal during the last 30 years, science has been institutionalized as a gendered profession.